Environmental Impact of Coal Mining: A case study on Barapukuria Coal Mining Industry, Dinajpur, Bangladesh - Hasan, MR; Rashid, H; Paul, AK (Journal of Environmental Science and Natural Resources, 2015)
The study revealed that the concentration of organic Carbon, K, Ca, Mg, P, S were 111.39 ppm, 555.31 ppm, 200.73ppm, 11.10 ppm, 220.20 ppm, 1.48 ppm respectively for coal water treated farm soil and 105.37 ppm, 145.09 ppm, 197.06 ppm, 6.16 ppm, 30.78 ppm, respectively for normal farmers field soil and BOD, DO, temperature in mine drainage water were 2.14 ppm, 2.44 ppm, 6.6 oC respectively. Thus the effect of coal water, discharged from Barapukuria coal mine area to the surrounding agricultural fields was found good for organic carbon, P, S, Ca, Mg fertility of soil but the continuous deposition of trace metals in the agricultural field soil may cause a serious deterioration of soil resources. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22120 J. Environ. Sci. & Natural Resources, 6(2): 207-212 2013